The relations among general intelligence, metacognition and text learning performance [Üstbiliş, zeka ve metinden öǧrenme performansi arasindaki ilişkiler] - (:unkn) unknown (Turkish Education Association, 2014)
The main aim of this study was to investigate the relations among text learning performance, general intelligence and the three components of metacognition; namely metacognitive knowledge, metacognitive monitoring and metacognitive control. The participants were 91 fifth graders. The results of the study indicated no significant correlations among metacognitive knowledge, metacognitive control and general intelligence. On the other hand, metacognitive monitoring and general intelligence correlated significantly. The results of the regression analysis showed that metacognitive knowledge did not contribute to students' text-learning performance whereas metacognitive monitoring and metacognitive control, together with general intelligence, were found to be significant predictors in explaining students' text-learning performance. © 2014 Eǧitim ve Bilim Dergisi.
Keywords: General intelligence; Metacognition; Metacognitive control; Metacognitive knowledge; Metacognitive monitoring; Text-learning